The Use of Dijkstra's Algorithm in Determining the Shortest Path of Expedition in Bandarlampung - Assiva, Adelia; Puspita, Resta Meyliana; Sihombing, Riska Romauli; Chasanah, Siti Laelatul; Mustika, Mira (Integra: Journal of Integrated Mathematics and Computer Science, 2024)
Delivery of goods is a problem faced by freight forwarders/expedition companies. Determining an efficient route will determine the speed and cost of delivery. This is faced by most expedition companies, including one of the expedition companies in the city of Bandarlampung, namely the J&T Express expedition. There are 20 J&T Express branches in Bandarlampung city. If someone wants to send an item but one of the branches is closed or not available then he will try to determine the next closest branch. In this study, the shortest path from J&T on Pagar Alam to 19 other branches in Bandarlampung will be determined using Dijkstra’s Algorithm.